Inventarisasi dan Studi Dispersal Gulma Asing Invasif di Kebun Biologi UIN Sunan Gunung Djati Bandung - Rahmawati, Tiara; Anggraeni, Wulan; Mustahiq Akbar, Rahmat Taufiq (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Invasive alien weeds are plant pests because they can interfere with the growth and productivity of surrounding plants. Studies of invasive alien weeds, inventory of species, and their dispersal are important not only in conservation environments but also in study areas in educational institutions such as universities. This research was conducted with the aim of being an initial study to determine the types and distribution vectors of invasive alien weeds in the study area of the biology garden of UIN Sunan Gunung Djati Bandung which have the potential to disrupt the surrounding ecosystem. Weed sampling was carried out by purposive sampling exploration method in the biology garden area of the Faculty of Science and Technology UIN Sunan Gunung Djati Bandung. Based on the inventory results, a total of 16 species and 8 families of invasive alien weeds were obtained with the most families coming from the Asteraceae family. The invasive alien weed seed dispersal vectors include wind, water, and animals. Most invasive alien weed species found in the sampling sites have wind and animal dispersal vector types (31.25%). Seed dispersal by animals and wind has an effective dispersal rate because the range of distribution is quite wide. In addition, the characteristics of seeds, the ability to adapt and develop in new environments in plants such as species of the Asteraceae family can cause their invasion to take place quickly and massively.